c-Abl Inhibition Exerts Symptomatic Antiparkinsonian Effects Through a Striatal Postsynaptic Mechanism - Zhou, Yu; Yamamura, Yukio; Ogawa, Masatoshi; Tsuji, Ryosuke; Tsuchiya, Koichiro; Kasahara, Jiro; Goto, Satoshi (Frontiers in Pharmacology, 2018)
Parkinson's disease (PD) is caused by a progressive degeneration of nigral dopaminergic cells leading to striatal dopamine deficiency. From the perspective of antiparkinsonian drug mechanisms, pharmacologic treatment of PD can be divided into symptomatic and disease-modifying (neuroprotective) therapies. An increase in the level and activity of the Abelson non-receptor tyrosine kinase (c-Abl) has been identified in both human and mouse brains under PD conditions. In the last decade, it has been observed that the inhibition of c-Abl activity holds promise for protection against the degeneration of nigral dopaminergic cells in PD and thereby exerts antiparkinsonian effects. Accordingly, c-Abl inhibitors have been applied clinically as a disease-modifying therapeutic strategy for PD treatment. Moreover, in a series of studies, including that presented here, experimental evidence suggests that in a mouse model of parkinsonism induced by N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, c-Abl inhibition exerts an immediate effect improving motor impairments by normalizing altered activity in striatal postsynaptic signaling pathways mediated by Cdk5 (cyclin-dependent kinase 5) and DARPP-32 (dopamine- and cyclic AMP-regulated phosphoprotein 32kDa). Based on this, we suggest that c-Abl inhibitors represent an ideal antiparkinsonian agent that has both disease-modifying and symptomatic effects. Future research is required to carefully evaluate the therapeutic efficacy and clinical challenges associated with applying c-Abl inhibitors to the treatment of PD.